Position of Fowler and Semi-fowler to Reduce of Shortness of Breath (Dyspnea) Level While Undergoing Nebulizer Therapy - Chanif, Chanif; Prastika, Dewi (University of Muhammadiyah Semarang, 2019)
Chronic obstruction pulmonary disease (COPD) is a lung disease that is caused due to an obstruction in a channel the airflow that much happening in Indonesia due to the high-risk factor exposure causes the onset of COPD as the habit of smoking and an unhealthy environment. Blockage in the airway that occurs in patients of COPD is usually characterized by shortness of breath. The various ways that can be done to overcome the shortness of breath are with nebulizer therapy. Nebulizer therapy action is undertaken in accordance with standard operating procedures (SPO) already determined, in the SPO mention the position at the time of the nebulizer therapy position fowler or semi fowler. This study aims to know the effectiveness of the grant the position of Fowler and semi fowler against the scale of the COPD patient shortness of breath while undergoing therapy nebulizer. Methode of this study is a quasy experiment in two groups using pre-test and post-test design. The study was conducted in General Hospital K.R.M. T Wongsonegoro Semarang with the total sample as many as 32 patients. The analysis using Mann Whitney with p-value 0.000 (p < 0.05) so that it can be concluded that there is a difference in the average scale of shortness of breath between fowler and semi fowler while undergoing group therapy nebulizer. The analysis showed that the position of semi fowler is more effective in lowering shortness of breath when compared to the position of fowler while undergoing therapy nebulizer. This study recommended giving the semi-fowler position to reduce dyspnea in COPD patients while undergoing Nebulizervtherapy.